2020
DOI: 10.3390/molecules25215177
|View full text |Cite
|
Sign up to set email alerts
|

Secondary S100B Protein Increase Following Brain Arteriovenous Malformation Rupture is Associated with Cerebral Infarction

Abstract: Early S100B protein serum elevation is associated with poor prognosis in patients with ruptured brain arteriovenous malformations (BAVM). The purpose of this study is to determine whether a secondary elevation of S100B is associated with early complications or poor outcome in this population. This is a retrospective study of patients admitted for BAVM rupture. A secondary increase of S100B was defined as an absolute increase by 0.1 μg/L within 30 days of admission. Fisher’s and unpaired t tests followed by mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, the expression of S100B may regulate cardiac metabolic function in the remodeling of the post-infarcted diabetic heart (Mohammadzadeh et al 2013 ). Moreover, secondary infarction caused by the rupture of cerebral arteriovenous malformation can cause secondary elevation of serum S100B protein level (Garzelli et al 2020 ).…”
Section: S100 Proteins In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the expression of S100B may regulate cardiac metabolic function in the remodeling of the post-infarcted diabetic heart (Mohammadzadeh et al 2013 ). Moreover, secondary infarction caused by the rupture of cerebral arteriovenous malformation can cause secondary elevation of serum S100B protein level (Garzelli et al 2020 ).…”
Section: S100 Proteins In Cardiovascular Diseasesmentioning
confidence: 99%
“…Ventricular remodeling after myocardial infarction (Tsoporis et al 2005b;Mohammadzadeh et al 2013) Cerebral infarction (Garzelli et al 2020) Atrial fibrillation (Zhang et al 2013;Scherschel et al 2019) Acute coronary syndrome (Cai et al 2011) Dilated cardiomyopathy (Mazzini et al 2007) Heart failure (Li et al 2011;Chen et al 2020) Myocardial infarction (Tsoporis et al 2010) Atherosclerosis (Wu et al 2019) Cerebral ischemia/reperfusion injury (Yuan et al 2019) Aortic aneurysm (Roberts et al 2021) Cardiac arrest (Deye et al 2020) contains the binding site of the target protein, exerting their biological effect by interacting with the target protein (Liu et al 2013). In addition to Ca 2+ , the functions of many S100 proteins can be regulated by binding zinc or copper ions (Weisz and Uversky 2020).…”
Section: S100bmentioning
confidence: 99%
“…Angiogenesis-associated proteins, such as VEGF (vascular endothelial growth factor), 9 MMP (matrix metalloproteinase), 10 inflammatory cytokines, 11 S100B (S100 calcium binding protein B), 12 etc, are highly overexpressed in bAVM nidus (Figure 2). Weinsheimer et al 13 have reported dysregulated VEGF, MAPK (mitogen-activated protein kinases), Wnt (wingless-related integration site), and Notch signaling in abnormal blood vessels.…”
Section: Protein Biomarkers Of Bavmmentioning
confidence: 99%